2016
DOI: 10.1002/mren.201600024
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Elongational‐Flow Microprocess for the Production of Size‐Controlled Nanoemulsions: Batch Operation

Abstract: Performances of a newly developed microprocess in producing size‐controlled nanoemulsions in the lower nanometer range are assessed. The microprocess comprises an elongational‐flow micromixer with a bore size of either 150, 250, or 500 μm. By inducing a reciprocating flow through the restriction of the micromixer, methyl methacrylate (MMA)‐based nanoemulsions with controlled sizes in the range 50–300 nm are successfully prepared at low pressures (ca. 2.5 bars) in laminar to intermediate hydrodynamic flow regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Table also shows that an oil phase composed of either pure TPGDA or a mixture of MMA and TPGDA (50 wt%) gives different nanoemulsion sizes (entries 9 and 10) when processed with the same parameters. This can be readily interpreted considering the two following reasons: (i) the difference in interfacial tensions between the two aforementioned oil phases; a larger nanodroplets size was obtained, as expected, with the highest interfacial tension and (ii) the viscosity difference between TPGDA and MMA: 14.5 cP versus 0.61 cP at 20 °C (suppliers data), respectively; since the former is the most viscous compound, it will be more difficult to elongate and break‐up TPGDA droplets as stressed out in our previous work …”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Table also shows that an oil phase composed of either pure TPGDA or a mixture of MMA and TPGDA (50 wt%) gives different nanoemulsion sizes (entries 9 and 10) when processed with the same parameters. This can be readily interpreted considering the two following reasons: (i) the difference in interfacial tensions between the two aforementioned oil phases; a larger nanodroplets size was obtained, as expected, with the highest interfacial tension and (ii) the viscosity difference between TPGDA and MMA: 14.5 cP versus 0.61 cP at 20 °C (suppliers data), respectively; since the former is the most viscous compound, it will be more difficult to elongate and break‐up TPGDA droplets as stressed out in our previous work …”
Section: Resultssupporting
confidence: 71%
“…Smaller nanodroplets were obtained when the former two parameters are increased or when the latter is decreased. In a previous study, we have shown that the higher the elongational strain rate (trueε˙) imposed by the sharp restriction of the micromixer, the smaller are the nanodroplets. Moreover we have demonstrated that trueε˙ is proportional to the reciprocating flow rate and inversely proportional to the microchannel size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, previous works have been conducted concerning the elongational-flow reactor and mixer aimed at investigating the effects of various process (pressure, number of cycles, geometry of mixing elements) and composition (amount of surfactant, volume fraction of dispersed phase) parameters on the droplet size for reference monomers (methyl acrylate and ethyl acrylate) and characteristics of subsequent polymeric nanoparticles obtained after UV irradiation. [17][18][19] In brief, the use of PNPs in therapeutic delivery, biotechnology, magnetic separation or diagnostic imaging would allow the combination of the advantages of inorganic charged particles (contrast agents, phase compatibilizers, electro-sensitivity) and the biocompatibility of polymers. So, we compared different emulsification-evaporation processes (sonication, shear mixing and elongational-flow micromixing) to demonstrate, for the first time, the possible one-step formation of polymeric charged nanoparticles from an already synthesized charged polymer.…”
Section: Introductionmentioning
confidence: 99%